1998
DOI: 10.1074/jbc.273.35.22819
|View full text |Cite
|
Sign up to set email alerts
|

Uteroglobin (UG) Suppresses Extracellular Matrix Invasion by Normal and Cancer Cells That Express the High Affinity UG-binding Proteins

Abstract: Uteroglobin (UG) is a steroid-inducible, multifunctional, secreted protein with antiinflammatory and antichemotactic properties. Recently, we have reported a high affinity UG-binding protein (putative receptor), on several cell types, with an apparent molecular mass of 190 kDa (Kundu, G. C., Mantile, G., Miele, L., CordellaMiele, E., and Mukherjee, A. B. (1996) Proc. Natl. Acad. Sci. U. S. A. 93, 2915-2919). Since UG is a homodimer in which the 70 amino acid subunits are connected by two disulfide bonds, we so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 64 publications
0
49
0
Order By: Relevance
“…Despite the rather low level of homology between uteroglobin and HIN-1, our data indicate that the two proteins seem to share quite similar functions. Both inhibit many features of the invasive phenotype, including anchorage-dependent and anchorageindependent growth, and invasion of extracellular matrix (12)(13)(14)(15). HIN-1 and uteroglobin ligand binding activity, suggesting putative receptor expression, exists on the same cell types that express these proteins, suggesting that they act in an autocrine manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the rather low level of homology between uteroglobin and HIN-1, our data indicate that the two proteins seem to share quite similar functions. Both inhibit many features of the invasive phenotype, including anchorage-dependent and anchorageindependent growth, and invasion of extracellular matrix (12)(13)(14)(15). HIN-1 and uteroglobin ligand binding activity, suggesting putative receptor expression, exists on the same cell types that express these proteins, suggesting that they act in an autocrine manner.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to HIN-1, the expression of uteroglobin is lost in the majority of lung and prostate cancers (11). Exogenous overexpression of uteroglobin in cancer cell lines results in reversion of many features of the transformed phenotype, including decreased anchorage-dependent and anchorage-independent growth as well as decreased ability to invade extracellular matrix (12)(13)(14)(15). Furthermore, mice with homologous deletion of the uteroglobin gene develop spontaneous tumors and show increased susceptibility to chemical carcinogen-induced lung cancer (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…However, UG expression in both malignant lung tumors originating from lung epithelia as well as in the cell lines derived from these tumors is either drastically suppressed or totally undetectable (22,23). Further, we demonstrated that UG prevents migration and extracellular matrix invasion of cancer cells in vitro (24).…”
mentioning
confidence: 96%
“…Accordingly, lymphoblast cells were transfected with IIS antisense oligonucleotides and used for chemotaxis assay. Conditioned medium from fibroblast cell culture was used as the chemoattractant, and cell migration and invasion assays were conducted as previously reported (32,33). The results show that chemotactic migration of antisense oligo-transfected cells was markedly inhibited compared with that of the control and sense oligonucleotide-transfected cells (Fig.…”
Section: Inhibition Of Iis Expression Prevents Lymphoblast Cell Migramentioning
confidence: 94%
“…The founding member of this protein family, UG, which is induced by IFN-␥, is also a secreted protein, and recently, we have demonstrated that UG binds to as-yet-unidentified cell surface binding protein(s) with high affinity and specificity and regulates cellular migration and invasion (32,33,43). Consistent with these findings, we find that IIS is also induced by IFN-␥, and the suppression of IIS expression by antisense oligonucleotide treatment of the cells inhibits chemotactic migration and invasion.…”
Section: Discussionmentioning
confidence: 99%